The Effect of Social Media Promotion, Product Price and Product Diversity on Consumer Purchase Decisions at M. Aboe Talib Coffee Shop in East Denpasar - I Ketut Wira Pranata; Ni Made Rustini; A.A. Ketut Jayawarsa (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze the influence of social media promotion, product price, and product diversity on consumer purchasing decisions at M. Aboe Talib Coffee Shop in East Denpasar. This study involved 99 respondents selected using random sampling techniques. Data were collected by distributing questionnaires to consumers of M. Aboe Talib Coffee Shop. The analysis method used was multiple linear regression with analysis stages including instrument validity and reliability tests, partial tests (t-tests), and simultaneous tests (F-tests). The results showed that social media promotion, product price, and product diversity partially had a positive and significant influence on consumer purchasing decisions. Simultaneously, these three variables also had a positive and significant influence on consumer purchasing decisions. Thus, social media promotion, product price, and product diversity have an important role in increasing consumer purchasing decisions at M. Aboe Talib Coffee Shop in East Denpasar.